Babesiosis in Cattle slaughtered at Zango Abattoir Zaria, Kaduna State, Nigeria: A Short Communication - Wada, Y; Tijjani, M; Abdulmalik, Y; Wada, M (UMYU Journal of Microbiology Research, 2020)
Babesiosis constitutes a major public health threat to cattle rearing in most countries, including Nigeria. This study was designed to determine the prevalence of Babesia sp. in cattle slaughtered at Zango abattoir. Blood samples were collected from 200 Cattle at slaughter in bottles containing EDTA and transported to the laboratory. A thin blood smear was made, air- dried, fixed in absolute methanol for 5 minutes and stained with 10% Giemsa. Slides were examined for Babesia spp. under oil immersion (x100) objective lens. An overall prevalence of 6.5% (13/200) was observed. Prevalence in males and females were 4.35% (3/69) and 7.63% (10/131) respectively and the differences in their prevalence rates were not significant (χ²=0.803, p value=0.370). Females had a higher chance of getting infected (OR=1.818, CI=0.483-6.838) than male (OR=0.550, CI=0.146-2.068). The prevalence in White Fulani 6.63% (12/181) was higher than that of Sokoto Gudali 5.26% (1/19) although not significant (χ²=0.053, P-Value=0.818). White Fulani had a higher chance of getting infected (OR=1.278, CI=0.157- 10.407) than Sokoto Gudali (OR=0.782, CI=0.096-6.371). The prevalence in cattle at > 8.5 years was 4.35% (3/69) as compared to 7.63 % (10/131) of cattle within 5-8.5 years. There was also no association between the age of cattle and the prevalence of Babesia (χ²=0.803, P value=0.370). Other haemoparasites observed were Anaplasma spp 16.5% (33/200), Theileriaspp11.0% (22/200) and Trypanosoma sp0.5% (1/200). This study has detected a low prevalence of Babesia in the study area. There is therefore the need for large scale studies and also studies using ELISA and PCR.